Determinants of students’ character and environmental concept mastery in biology learning - Arifah Novia Arifin; Asham Bin Jamaluddin; H. Hardianto; Abd. Muis; Noviansyah Kusmahardhika (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
This study explores the joint influence of sociocultural understanding, science literacy, psychomotor skills, and learning approach on the development of students’ character along with their conceptual understanding of environmental change. Using a quantitative explanatory design, this study utilized Structural Equation Modeling (SEM) to analyze data from a total of 837 high school students in South Sulawesi, Indonesia. The findings of this study show that sociocultural understanding significantly influences students’ character development. However, it does not appear to influence conceptual understanding. Meanwhile, science literacy has a dominant influence on both sociocultural understanding and character development. Learning approach significantly influences character development but negatively impacts conceptual understanding. These findings underscore the importance of integrative education, which incorporates cultural responsiveness, science literacy, and experiential learning to holistically enhance ethical values, cognitive skills, and practical competence. This study provides new insights into sustainable teaching strategies, highlighting their role in guiding individuals to be responsible for environmental change and scientifically literate.